Pharmacological attributes of Bacopa monnieri extract: Current updates and clinical manifestation - Fatima, Urooj; Roy, Sonam; Ahmad, Shahnawaz; Ali, Sabeeha; Elkady, Wafaa M.; Khan, Ilyas; Alsaffar, Rana M.; Adnan, Mohd; Islam, Asimul; Hassan, Md. Imtaiyaz (Frontiers in Nutrition, 2022)
Bacopa monnieri has been used for centuries in Ayurvedic medicine, alone or in combination with other herbs, as a memory and learning enhancer, sedative, and anti-epileptic. This review aimed to highlight the health benefits of B. monnieri extracts (BME), focusing on anti-cancer and neurodegenerative diseases. We examined the clinical studies on phytochemistry and pharmacological application of BME. We further highlighted the mechanism of action of these extracts in varying types of cancer and their therapeutic implications. In addition, we investigated the underlying molecular mechanism in therapeutic interventions, toxicities, safety concerns and synergistic potential in cognition and neuroprotection. Overall, this review provides deeper insights into the therapeutic implications of Brahmi as a lead formulation for treating neurological disorders and exerting cognitive-enhancing effects.